Peningkatan Kemampuan Membaca Al-Quran Menggunakan Metode Qiroati di TPQ Al-Auliya Rantewringin, Buluspesantren - Taqwawati, Annisa; Fatimah, Siti; Eliyanto, Eliyanto; Faisal, Faisal; Arifah, Umi (Tarbi: Jurnal Ilmiah Mahasiswa, 2024)
This study aims to determine the increase in children’s ability to read the quran according to the tajwid and makharijul letters using the qiroati method at TPQ AL-AULIYA Rantewringin. This research with Class Action Research was conducted for two cycles, which consisted of two meetings. Each cycle consists of planning, implementing, observing and reflecting. The research subjects were student of the quran class at TPQ AL-AULIYA Rantewringin. Data collection techniques using observation, interviews, documentation and tests. The results of data analysis in cycle I showed that as many as 56% of the children obtained a complete score in learning the law of tajwid and makharijul letters using the qiroati method. Whereas in cycle II as many as 87% of the children obtained a complete score. So it can be concluded that there is an increase in reading quran according to the tajwid and makharijul letters